Explaining Financial Technology Adoption Among Micro-Businesses: Evidence from An Integrated TAM-TPB Framework - Moch. Fadjar B. Saidia; Hais Dama; Herlina Rasjid (Department of Islamic Banking, 2026)
Purpose – This Study aims to explain financial technology adoption among microbusinesses in Gorontalo City: evidence from an integrated TAM-TPB framework. Methodology – The sampling technique in this study uses the Slovin formula. The data collection technique in this study is primary data collection. The population in this study comprises 11,806 micro-business actors in Gorontalo City, with a total sample of 99 respondents. The analysis is performed using SPSS 23. Findings – Partial tests (t-test) show that perceived ease of use and effectiveness positively and significantly influence Financial Technology usage, while risk has no significant effect. Simultaneously (F-test), all variables significantly influence FinTech use. The coefficient of determination (R²) is 0.481 (48.1%), indicating that 51.9% of FinTech usage is explained by other factors not examined in this study. Implications– The study confirms the applicability of integrating TAM and TPB in the context of micro-enterprises. Practically, it highlights the critical need for FinTech developers and policymakers to prioritise risk-mitigation strategies, enhance security features, and foster digital financial literacy to build trust and accelerate digital adoption among micro-business actors. Originality– This study showed a comprehensive framework that bridges TAM and TPB, uniquely demonstrating how perceived risk interacts with usability and effectiveness to shape the digital financial behaviours of micro-business actors.